Despenalización del aborto por males congénitos, cuando estos afecten la calidad de vida del nasciturus. - Quizhpe Sucunuta, Joselyn Anahi (2023)
The present work of Curricular Integration was carried out in response to the lack of concern for pregnant women whose fetus has been diagnosed with a congenital condition that affects their quality of life, or in other words, is incompatible with life, and who would like to be able to terminate their pregnancy for these reasons. In addition, the work that has been developed today has been driven by the numerous cases of mental and emotional instability of pregnant women due to the knowledge of the condition of their fetus and even more so when they witness the product of their womb perish. For the above mentioned, this research is based on the collection of various research materials that have served as support for the proper development of the same, such as digital and physical bibliographic references, in addition, both national and international legislation has served as analysis to expand the foundations that are set out throughout the research. In the same sense and to continue with the corresponding line of research, different methods have been used, such as: analytical, scientific, comparative, synthetic, statistical, inductive and deductive. Continuing with the use of research tools, use was also made of documentary techniques that served as a means of demonstrating how the central problem of the research severely affects pregnant women, on which the presentation and case studies were based. In the same way, and in conjunction with the cases presented, surveys were applied to legal professionals, specifically judges in criminal matters, in order to find out their criteria as operators of justice in relation to the issue that is of interest to us today. In addition, interviews were conducted with obstetricians, whose expertise in medicine helped to achieve a greater degree of certainty with respect to the arguments that underpin the development of the research. The aforementioned research methods and techniques have served as the basis and foundation for the completion of this project. In the same way, the doctrinal and legal criteria were necessary elements for a better understanding of the topics contained in the research. Thus, all of the aforementioned together served as a means to reach different objectives and conclusions, and to finally be able to offer a proposal and recommendations that, in the future, will benefit pregnant women whose fetus has been diagnosed with a congenital disorder that affects its quality of life, this avoiding the suffering of the unborn child and reducing the impact and trauma to the pregnant mothers.